Characteristic Of Environmental Sanitation in Family With Stunting Children Under Five Years Of Age - Endah Kusuma Wardani; Lutvia Dwi Rofika (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Attention to malnutrition has increased in recent decades, one of which is stunting. The nutritional problem that is currently being highlighted in the world is stunting where there are around 161 million children experiencing stunting. Stunting is a measure of short height compared to age. Factors causing stunting consist of direct and indirect causes, one of which is from the aspect of environmental sanitation, namely access to clean water, sanitation and hygiene. This study aims to provide an overview of the characteristics of environmental sanitation in families with stunting children under five years of age in the Klatak and Wonosobo Public Health Centers, Banyuwangi. This research is a descriptive study and a case series design. The research subjects used were 60 stunting toddlers with proportional random sampling as the sampling technique. The variables in this study were environmental sanitation, which consisted of access to clean water, ownership of clean water facilities, ownership of bathrooms, ownership of latrines, and ownership of cattle pens. The research instrument used a questionnaire to measure the characteristics of respondents and environmental sanitation conditions, interview guidelines, observation sheets, KIA books, and weighing month reports. The data was processed using descriptive analysis. The results depicted in this study are that most of the research subjects live in families that have access to clean water, have bathrooms and latrines, but also in families who have cattle pens close to the main house. Monitoring of ownership, use, and maintenance of access to clean water, latrines, bathrooms, and livestock cages in the home environment must be carried out properly so that it can become one of the strategies in preventing stunting under five. Prevention of contamination of water, soil, and air quality is one of the ways in preventing stunting in toddlers so that toddlers can develop optimally according to their age and growth period.